An Analysis of The Influence of Sharia Financial Literacy on Interest in Using Sharia Bank Products - Putri Nuraini; Mohammadtahir Cheumar (Sekolah Tinggi Ekonomi dan Perbankan Islam Mr. Sjafruddin Prawiranegara, 2023)
This study aims to analyze the influence of Sharia financial literacy on the interest in using Sharia bank products of mosque youth in Pekanbaru City, Riau. The sample of the study consists of 92 respondents. The type of this study is field research with a quantitative approach. The data are obtained from primary data with the analysis techniques using simple linear regression with data processing performed by SPSS Software Version 25. The hypothesis testing of the study is partial analysis (t-test). The results of the study show that the Sharia financial literacy has a positive and significant influence on the interest of mosque youth in Pekanbaru City to use Sharia bank products. It is proved by the t-value of the Sharia financial literacy variable (X) of 6.215 and the t-table value of 1.661, it can be seen that: t-count > t-table (6.215 > 1.671) with a significance level of 0.000 <0.05. Furthermore, the influence of the independent variable (Sharia financial literacy) on the dependent variable (interest) is 53.2%, while the remaining 46.8% is influenced by other variables not included in this study. Keywords: Sharia Financial Literacy, Interest, Sharia Bank Products.